2000
DOI: 10.1210/mend.14.9.0517
|View full text |Cite
|
Sign up to set email alerts
|

Selective Alterations in Organ Sizes in Mice with a Targeted Disruption of the Insulin-Like Growth Factor Binding Protein-2 Gene

Abstract: Insulin-like growth factor binding protein 2 (IGFBP-2) is one member of the family of IGF binding proteins believed to have both endocrine functions elicited by modulating serum IGF half-life and transport as well as autocrine/paracrine functions that result from blocking or enhancing the availability of IGFs to bind cell surface receptors. To clarify the in vivo role of IGFBP-2, we have used gene targeting to introduce a null IGFBP-2 allele into the mouse genome. Animals homozygous for the altered allele are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Previous studies have shown that most rodent fetal tissues/cell types produce multiple IGFBPs (8 -15). In comparison, there is little overlap in the expression domains of different IGFBPs during zebrafish embryogenesis (5,33,37) (this study). Second, disruption to the expression of one component of the IGF system often influences the expression of other IGF family members in the mouse model (33,52).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Previous studies have shown that most rodent fetal tissues/cell types produce multiple IGFBPs (8 -15). In comparison, there is little overlap in the expression domains of different IGFBPs during zebrafish embryogenesis (5,33,37) (this study). Second, disruption to the expression of one component of the IGF system often influences the expression of other IGF family members in the mouse model (33,52).…”
Section: Discussionmentioning
confidence: 72%
“…In comparison, there is little overlap in the expression domains of different IGFBPs during zebrafish embryogenesis (5,33,37) (this study). Second, disruption to the expression of one component of the IGF system often influences the expression of other IGF family members in the mouse model (33,52). For instance, it was reported that serum levels of IGFBP-1, -3, and -4 were increased in IGFBP-2 knock-out mice (33).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations